Vladimir Radunsky. A Portrait of the Artist in Context - Sharon Lee COWAN (Sztuka i Dokumentacja)
Five years after the passing of artist and illustrator Vladimir Radunsky, the article draws a portrait of this complex figure in the context of his life and migrations. Born in Russia, in 1954, Radunsky embraced illustration after difficult vocational junctures. The major hinge points in his artistic life were his two emigrations. The first, in 1982 at the age of 28, catapulted him from a grim USSR to New York City. Eighteen years later and now an accomplished artist and illustrator, Radunsky moved permanently to Italy. This geographic zigzag divides his life into three distinct periods, each generating accretions of cultural heritage that inform his artistic oeuvre. The article also addresses the impact on Radunsky’s work of his Russian-Jewish childhood, and sets the artist in the context of an oft-forgotten wave of global Jewish migration and the American political movement that supported it.